2020
DOI: 10.1016/j.amsu.2020.08.048
|View full text |Cite
|
Sign up to set email alerts
|

A review of management options for splenic artery aneurysms and pseudoaneurysms

Abstract: Background A review of the management of splenic artery aneurysms (SAA). There is no general consensus as to when and what type of intervention should be chosen to treat SAAs. The aim of this study is to investigate the types of intervention for SAAs including complication, reintervention, rupture, mortality after intervention of SAA in a review. Method A literature search was performed using “keywords” in Medline and Embase limited to publications from 2008 to 2018. 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Moreover, the onset of splenic infarction after SA occlusion may be well tolerated by the patient, which are usually asymptomatic, and their conditions can be managed non-surgically. 1,9 Therefore, this combination technique is a safe and effective approach for aberrant SAA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the onset of splenic infarction after SA occlusion may be well tolerated by the patient, which are usually asymptomatic, and their conditions can be managed non-surgically. 1,9 Therefore, this combination technique is a safe and effective approach for aberrant SAA.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 SAAs are often asymptomatic and incidentally identified. 1,9 However, the aberrant SAAs usually originate from the proximal SMA behind the pancreas, and the retroperitoneal plexus may be compressed by the aberrant aneurysm. Authors have reported that 41.5% patients with aberrant SAAs complained of epigastric pain or discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rupture could cause hemorrhagic shock leading to death. When splenic artery aneurysms are suspected, angiography is the gold standard for diagnosis [ 8 ]. Generally, SAA is diagnosed with CT angiography which enables arterial reconstruction and appreciates its features and location [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of splenic artery aneurysms depends on their size, location, and presenting symptoms [ 8 ]. Splenic artery aneurysms are indicated for treatment in the following situations: Symptomatic patients, asymptomatic with lesions >2 cm [ 7 ], pregnant women, or women of childbearing age with SAA > 1 cm.…”
Section: Discussionmentioning
confidence: 99%